Uruguay : First Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria; Staff Report; Staff Statement; Press Release; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2005)
Uruguay's First Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria are discussed. Growth has slowed from the strong post-crisis recovery, and inflation has remained subdued. Export growth has been strong, and although a sharp recovery in imports contributed to an increase in the external current account deficit, capital inflows have helped raise international reserves. The government is developing a broad agenda of growth-enhancing reforms, focused on attracting more private investment as the key engine of future growth and social progress in Uruguay.